Segmental hair analysis to assess effectiveness of single-session motivational intervention to stop ethanol use during pregnancy. (1st January 2016) - Joya, Xavier; Mazarico, Edurne; Ramis, Juan; Pacifici, Roberta; Salat-Batlle, Judith; Mortali, Claudia; García-Algar, Oscar; Pichini, Simona
Graphical abstract: Flow chart of pregnant women enrolled in the Educational Control Condition (ECC) and Motivational Intervention (MI) performed at the end of the first pregnancy trimester. Hair EtG concentrations were measured each trimester of gestation and participants were classified according their alcohol consumption status. Grey boxes indicate the group of women in which ECC or MI therapy was effective and presented hair EtG concentrations below 7 pg/mg. Highlights: We tested single-session motivational intervention (MI) to stop gestational ethanol. We used maternal hair analysis of ethyl glucuronide (EtG) to verify drinking behavior. MI did not significantly increase abstinence in pregnant women who previously drunk. Single-session MI was not enough to stop ethanol use during pregnancy. Interventions at any visit during pregnancy are recommended. Abstract: Background: This study aimed to test the effectiveness of single-session motivational intervention to stop ethanol use during pregnancy using segmental hair analysis of ethyl glucuronide to objectively verify drinking behavior before and after intervention. Methods: 168 pregnant women attending Hospital del Mar (Barcelona, Spain) for antenatal visit were included in the study and randomly assigned to one of two conditions: single-session motivational intervention (MI; N = 83) or single-session educational control condition (ECC; N = 85). Ethyl glucuronide was measured in maternal hair divided into three segments of 3 cm each corresponding to the three different gestation trimesters by a validated liquid chromatography tandem mass spectrometry method. Concentrations of EtG < 7 pg/mg, between 7 and 30 pg/mg and ≥30 pg/mg in each segment were used to assess total abstinence, repetitive moderate drinking and chronic excessive consumption in the previous three months. Results: About a third of pregnant women self-reporting no ethanol consumption during gestation showed hair EtG values corresponding to ethanol drinking. Single-session MI helped in decreasing alcohol consumption during pregnancy as assessed by lower hair EtG concentrations in 2nd and 3rd trimesters. However, it did not significantly increase complete abstinence in pregnant women who previously showed hair EtG compatible with ethanol consumption. Conclusions: Pregnant women did not correctly self reported ethanol consumption during gestation, while hair EtG was essential to correctly identify drinking patterns. Single-session MI was not enough to stop ethanol use during pregnancy. Interventions at any visit during pregnancy are strongly recommended.